2011
DOI: 10.1007/s00415-011-6099-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory 7-Tesla magnetic resonance spectroscopy in Huntington’s disease provides in vivo evidence for impaired energy metabolism

Abstract: Huntington’s disease (HD) is a neurodegenerative genetic disorder that affects the brain. Atrophy of deep grey matter structures has been reported and it is likely that underlying pathologic processes occur before, or in concurrence with, volumetric changes. Measurement of metabolite concentrations in these brain structures has the potential to provide insight into pathological processes. We aim to gain understanding of metabolite changes with respect to the disease stage and pathophysiological changes. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 32 publications
5
55
1
Order By: Relevance
“…An exploratory in vivo 7T MRS study characterized metabolite changes with respect to disease stage and pathophysiological changes in Huntington’s disease (HD) in three tested groups: premanifest gene carriers, manifest HD patients, and healthy volunteers (Figure 1) 13 . In the caudate nucleus and the putamen, manifest HD patients showed significantly reduced NAA ( p = 0.009 and 0.024) and Cr ( p = 0.001 and 0.027), compared with healthy volunteers.…”
Section: Degenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory in vivo 7T MRS study characterized metabolite changes with respect to disease stage and pathophysiological changes in Huntington’s disease (HD) in three tested groups: premanifest gene carriers, manifest HD patients, and healthy volunteers (Figure 1) 13 . In the caudate nucleus and the putamen, manifest HD patients showed significantly reduced NAA ( p = 0.009 and 0.024) and Cr ( p = 0.001 and 0.027), compared with healthy volunteers.…”
Section: Degenerative Disordersmentioning
confidence: 99%
“…Five different regions are displayed: hypothalamus, thalamus, caudate nucleus, putamen, prefrontal region. A Gaussian filter of 4 Hz was applied 13 .…”
Section: Figurementioning
confidence: 99%
“…In addition to providing new insights into the disease process, these results provide a new candidate biomarker. Two recent proton magnetic resonance spectroscopy studies in HD patients, one at 3 T and the other one at 7 T, as well as earlier studies at lower magnetic field cited in those two papers, showed that significant neurochemical changes in HD brain occur only after the appearance of clinical symptoms (Sturrock et al, 2010;van den Bogaard et al, 2011). Therefore, further studies are now needed to determine how early changes in pH reported by Chaumeil et al (2012) occur in HD and whether pH is a sensitive biomarker at earlier stages of the disease and in presymptomatic individuals.…”
mentioning
confidence: 95%
“…However, several studies have also used two-dimensional chemical shift imaging (2D-CSI) [33,40,41]. Studies measuring changes by MRS revealed different values of metabolite concentrations in patients with HD [34,35,42,43]. Recently, several longitudinal clinical studies have been performed.…”
Section: Magnetic Resonance Imaging (Mri) and Spectroscopy (Mrs)mentioning
confidence: 99%
“…Concentrations of metabolites, such as N-acetylaspartate, creatine, phosphocreatine, glutamate, glutamine, choline-containing compounds, inositol, γ-aminobutyric acid and others, can be determined by 1 H MRS [34]. 1 H MRS has previously been considered as a biomarker method in pre-manifest and early stages of HD [35][36][37].…”
Section: Magnetic Resonance Imaging (Mri) and Spectroscopy (Mrs)mentioning
confidence: 99%